ICPSEA3 2013: The 3rd International Conference on the Palaeontology of South-East Asia - Choong Chee Meng, Avalon Chin Soon Mun, Nurul Aishah Hanafi, Ask, . (2013)
The abstracts in this volume have been edited but have not been peer-reviewed